An Exploratory Study on Value Co-creation in High Education with a Focus on Interactions: A Case Study of the University of Nottingham from a Consumer Perspective - Gu, Qinyan (2019)
In the course of the marketisation of UK higher education, the relationship between the institutions and the students has gradually been transformed to that between service providers and consumers. Being in the market, the universities become increasingly exposed to global competition and their business performance is more easily affected by students’ satisfaction with the service they provide. To cope with the intense competition and meet students’ expectations, it is essential for UK higher education institutions to comprehensively understand students’ university experiences and ensure the quality of the service. Recent studies have suggested that the joint creation of value, which allows students to collaborate with universities to co-construct unique study experiences, may be of crucial importance in improving their perceived value of the university service. Using a case of the University of Nottingham, the research aims to investigate value co-creation in higher education with a focus on interactions, exploring the students’’ specific points of interactions in their university experiences, analyzing the way the university and students co-create value through interactions and identifying the factors that facilitate or inhibit interactive value co-creation in the context of higher education.